Roles of macrophages in lupus nephritis - Cheng, Yaqian; Liu, Lulu; Ye, Yufei; He, Yingxue; Hu, Wenwen; Ke, Haiyan; Guo, Zhi-Yong; Shao, Guojian (Frontiers in Pharmacology, 2024)
LN is a serious complication of systemic lupus erythematosus (SLE), affecting up to 60% of patients with SLE and may lead to end-stage renal disease (ESRD). Macrophages play multifaceted roles in the pathogenesis of LN, including clearance of immune complexes, antigen presentation, regulation of inflammation, and tissue repair. Macrophages are abundant in the glomeruli and tubulointerstitium of LN patients and are positively correlated with serum creatinine levels and the severity of renal pathology. It has been shown that the infiltration of macrophages is closely associated with several clinical indicators, such as serum creatinine and complement C3 levels, anti-dsDNA antibody titers, Austin score, interstitial fibrosis and renal tubular atrophy. Moreover, cytokines expressed by macrophages were upregulated at LN onset and downregulated after remission, suggesting that macrophages may serve as markers of LN pathogenesis and remission. Therapies targeting macrophages have been shown to alleviate LN. There are two main types of macrophages in the kidney: kidney-resident macrophages (KRMs) and monocyte-derived macrophages (MDMs). KRMs and MDMs play different pathological roles in LN, with KRMs promoting leukocyte recruitment at sites of inflammation by expressing monocyte chemokines, while MDMs may exacerbate autoimmune responses by presenting immune complex antigens. Macrophages exhibit high plasticity and can differentiate into various phenotypes in response to distinct environmental stimuli. M1 (proinflammatory) macrophages are linked to the progression of active SLE, whereas the M2 (anti-inflammatory) phenotype is observed during the remission phase of LN. The polarization of macrophages in LN can be manipulated through multiple pathways, such as the modulation of signaling cascades including TLR 2/1, S1P, ERS, metabolic reprogramming, and HMGB1. This paper provides a comprehensive overview of the role of macrophages in the progression of lupus nephritis (LN), and elucidates how these cells and their secretory products function as indicators and therapeutic targets for the disease in the context of diagnosis and treatment of LN.